Некоторые инварианты электрического взрыва проводников в оптимальных режимах - Хайнацкий, Сергей Александрович (НТУ "ХПИ", 2016)
Получены некоторые инварианты электрического взрыва проводников в оптимальных режимах, когда вся запасенная энергия выделяется в первом полупериоде. Показано, что в оптимальных режимах ряд соотношений – отношение запасенной энергии к массе проводника, к энергии сублимации, отношение волнового сопротивления разрядного контура и начального омического сопротивления проводника, не зависят от параметров контура и размеров проводников. Определено среднее значение отношения начального напряжения к длине проводника, зависящее только от собственной частоты разрядного контура. Установлены границы применимости модели однородного взрыва проводников.

The objective of the research was to find the variables which characterize features of the electrical explosion of conductors in optimal modes (with all stored energy released in the first half-cycle) and which aren’t dependent on the electrical parameters of the energy source and geometrical sizes of the conductor, i.e. are invariant to their change. Optimality conditions obtained earlier using experimentally determined criteria of similarity (invariants of similarity) of electrical characteristics of the explosion of conductors were used. It was shown that in optimal modes a number of dependencies – the dependence of the stored energy on the mass of the conductor and on the sublimation energy, the dependence of the wave resistance of the discharge circuit on the initial ohmic resistance of the conductor – depend only on the variables characterizing thermal and electrotechnical properties of the conductors’ metal. Based on acquired dependencies, the average value of the ratio of the initial voltage on the length of the conductor which depends only on the natural frequency of the discharge circuit was determined. Limitations of the applicability of the model of homogeneous explosion of conductors were defined.
Some invariants of the electrical explosion of conductors in optimal modes
Keywords: инварианты подобия; электроразрядный контур; ЭВП; магнитогидродинамические неустойчивости; invariants of similarity; electrical discharge circuit